The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.crvi.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the major American snake radiation: A molecular phylogeny of the Dipsadidae Bonaparte (Serpentes, Caenophidia)

Abstract: The Dipsadidae contains more than 700 extant species belonging to 92 genera and is the largest family of American snakes. In this work, we built a data set including two mitochondrial genes (12S and 16S rRNA) for 125 dipsadid taxa belonging to 59 genera, in order to gain further insights on the phylogenetic relationships of this large group at the subfamilial and generic levels. Among dipsadines, the monotypic genus Nothopsis is the sister-group to Leptodeira. Among xenodontines, the monophyly of seven previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
118
2
31

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(169 citation statements)
references
References 36 publications
15
118
2
31
Order By: Relevance
“…The Xenodermatinae (Clade 2; represented by Xenodermus and Stoliczkia) is a basally diverging clade among caenophidians in our study, as well as Kelly et al (2003), Vidal & Hedges (2002a,b), and Vidal et al (2008). Some other molecular studies (e.g., Lawson et al, 2005;Kelly et al, 2009) found a radically different phylogenetic position for xenodermatines based on molecular sequences for Oxyrhabdium, which is typically included within this group.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…The Xenodermatinae (Clade 2; represented by Xenodermus and Stoliczkia) is a basally diverging clade among caenophidians in our study, as well as Kelly et al (2003), Vidal & Hedges (2002a,b), and Vidal et al (2008). Some other molecular studies (e.g., Lawson et al, 2005;Kelly et al, 2009) found a radically different phylogenetic position for xenodermatines based on molecular sequences for Oxyrhabdium, which is typically included within this group.…”
Section: Discussionmentioning
confidence: 43%
“…Subsequently, Pinou et al (2004) applied the resurrected name "Elapoidea" to a clade comprising Atractaspis + Elapidae. "Elapoidea" has subsequently been used for "Clade A" of Lawson et al (2005) in several molecular phylogenetic studies (Vidal et al, 2007(Vidal et al, , 2008; Kelly et al, 2009; see also our results below). Clade B of Lawson et al (2005) was referred to as "Colubroidea" by Pinou et al (2004) and subsequent authors.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations